2003
DOI: 10.1002/ana.10743
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid increases SMN levels in spinal muscular atrophy patient cells

Abstract: Spinal Muscular Atrophy (SMA) is caused by diminished Survival of Motor Neuron (SMN) protein, leading to neuromuscular junction (NMJ) dysfunction and spinal motor neuron (MN) loss. Here, we report that reduced SMN function impacts the action of a pertinent microRNA and its mRNA target in MNs. Loss of the C. elegans SMN ortholog, SMN-1, causes NMJ defects. We found that increased levels of the C. elegans Gemin3 ortholog, MEL-46, ameliorates these defects. Increased MEL-46 levels also restored perturbed microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
186
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(197 citation statements)
references
References 32 publications
8
186
0
3
Order By: Relevance
“…In vitro experiments with phenylbutyrate (PBA) and valproic acid (VPA) -two well-known HDACi -have shown an increase in SMN mRNA and protein levels in SMA fibroblasts. [15][16][17] Similar studies with hydroxyurea (HU) in EBV-immortalized SMA lymphoblasts 18 have shown an increase in the FL-SMN/D7-SMN (FL/D7 ratio). Pilot trials with these drugs have been performed in SMA patients and results were promising, [19][20][21] leading to the development of placebo-controlled clinical trials.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…In vitro experiments with phenylbutyrate (PBA) and valproic acid (VPA) -two well-known HDACi -have shown an increase in SMN mRNA and protein levels in SMA fibroblasts. [15][16][17] Similar studies with hydroxyurea (HU) in EBV-immortalized SMA lymphoblasts 18 have shown an increase in the FL-SMN/D7-SMN (FL/D7 ratio). Pilot trials with these drugs have been performed in SMA patients and results were promising, [19][20][21] leading to the development of placebo-controlled clinical trials.…”
Section: Introductionmentioning
confidence: 74%
“…34 Two to ten percent of genes are believed to be regulated by histone acetylation and deacetylation, 35 but we do not know whether these compounds upregulate SMN2 by increasing histone acetylation at the SMN promoter, or by activating the acetylation state of a critical transcription factor. 17 Kernochan et al 36 observed that even though acetylated H3 and H4 histones predominated in the transcriptional origin of the SMN gene, VPA treatment led to acetylation in farupstream regions where there are usually fewer acetylated H3 and H4 histones. Further research will help to clarify the mechanism of action and individual response to these compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these promising experimental approaches, no readily available effective treatment for SMA exists to date. 19,20 Targeting SMN2 gene transcription by use of histone deacetylase inhibitors (HDACi) such as valproic acid (VPA), Trichostatin A, SAHA, sodium butyrate, LBH589 or M344 [21][22][23][24][25][26][27][28] is an approach with potentially fast clinical implementation. Moreover, HDACi treatment has previously been shown to increase SMN2 transcription and to ameliorate the phenotype in SMA mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC-inhs have been tested in vitro and in vivo: hydroxybutyric acid was the first compound shown to increase SMN2 levels in lymphoblastoid cell lines from SMA patients and to also increase the lifespan of a SMA mice [Chang et al, 2001]. Since then, valproic acid, phenylbutyrate, trycostatin A, and SAHA have also been shown to increase SMN levels in vitro and/or to improve the survival of SMA models in pre-clinical studies [Brichta et al, 2003;Sumner et al, 2003;Andreassi et al, 2004;Hahnen et al, 2006;Avila et al, 2007;Narvel et al, 2008;Riessland et al, 2010]. Valproic acid and phenylbutyrate have been tested in patients with SMA but with discordant outcomes.…”
Section: Sma Treatment: How When and Where?mentioning
confidence: 99%